Shia Armed Groups and the Future of Iraq - Rached, Kardo; Bali, Ahmed Omar (International Studies. Interdisciplinary Political and Cultural Journal, 2019)
The rising and acceleration of the Shia armed group in Iraq, Syria, Yemen, and Lebanon require a deep understanding of the root of the multi-dimensional conflicts in the Middle East. An appropriate and sufficient approach to the research about these militias will be from an internal conflict rather than an external conflict. The legitimization for the existence of the majority of these militias if not all of them is to fight and struggle against an entity which is the Sunni sect, in this case, that will assimilate them not integrate them peacefully.